Aplicação continuada de dejetos animais por 17 anos e toxidez em plantas de milho: avaliação da dinâmica de Cu, Zn e Mn em solo e planta - Oliveira, Anelisi Inchauspe de (2023)
Animal waste is often used in agriculture to provide macronutrients to crops and to dispose of residues from intensive farming. However, these inputs may have unbalanced levels of nutrients, being a potential soil contaminant, especially for micronutrients such as trace metals. The collections were carried out in an experimental area with 17 years of animal manure and mineral fertilizer applications. The treatments employed are liquid bovine manure (CS), liquid pig manure (PL), swine deep litter (PDL), mineral fertilizer (NPK) and treatment without fertilization (control). Thus, the objective of this work was to evaluate the dynamics of Cu, Zn and Mn in the soil-plant relationship during the development of the corn crop in an Typic Hapludalf submitted to 17 years of animal manure applications. The soil analyzes carried out were available levels of Cu, Zn and Mn by HCl, Mehlich-1 and Mehlich-3 extractors and sequential extraction for the same elements in rhizosphere and non - rhizosphere soil. For corn plants, nitroperchloric digestion of the root and aerial part, and subcellular division of the leaves were performed. Manure treatments significantly increased Cu and Zn contents in soil and maize plants. Mn was not significantly affected by the fertilizers, showing signs of toxicity, due to accumulation in subcellular organelles in the treatment with mineral fertilizer. In addition, the availability of metals was affected by the action of the roots, which acted in their regulation, modifying the characteristics of the rhizospheric soil, compared to the non-rhizospheric one. In general, organic matter increased by manure and root exudates play a key role in controlling nutrient availability.